Content Strategy in Technical Communication, 1st edition - Getto, Guiseppe (Routledge, 2020)
Content Strategy in Technical Communication provides a balanced, comprehensive overview of the current state of content strategy within the field of technical communication while showcasing groundbreaking work in the field.